Energia eólica e solar fotovoltaica no contexto de universalização e diversificação da matriz de geração brasileira - Franciscatto, Anderson (2005)
This work presents an investigation of the most suitable scenarios for the generation of electrical energy from wind power and photovoltaic sources, focusing the changes that occur in the Brazilian electrical sector in the current scenario of economic and social development. The work was developed in a structure oriented to quality and productivity and instigates the use of these sources as a contribution to the supply of electrical energy, as well as the opportunity of the diversification to contribute to the sustainability and universal access by the whole population. As a means of information, the following elements were investigated: the increase of supply and demand of electrical energy compared to GNP (Gross National Product), the external dependance of electrical energy, the make-up of the matrix of electrical energy generation, universalization indices, human development indices and the quality of the supplied electrical energy. The results of this work show the following aspects: there is a relation between the GNP increase and the supply and demand of electrical energy; the production of electrical energy by the approached renewable sources has specific scenarios, with specific regulamentation and particular conditions of application; the indices of universalization can be easily reached making use of these sources; the wind power is a strategic investment for the country; the areas with the lowest human development index also suffer from the worst quality of supplied energy; low human development indices also have a relation with the no access to electrical energy; the regions with less development will be the last ones to be assisted by the universalization project 2004-2015.